Assessment of biogeographic variation in traits of Lewis flax (Linum lewisii) for use in restoration and agriculture. Issue 2 (4th February 2022) - Innes, Peter; Gossweiler, André; Jensen, Scott; Tilley, Derek; St. John, Loren; Jones, Thomas; Kitchen, Stanley; Hulke, Brent S
Abstract: Lewis flax ( Linum lewisii ) is widely distributed across western North America and is currently used in native ecosystem restoration. There is also growing interest in de novo domestication of Lewis flax as a perennial oilseed crop. To better understand this species and facilitate both restoration and domestication, we used common gardens to assess biogeographical variation in a variety of seed and growth traits from 37 flax accessions, consisting of 35 wild populations from the Intermountain West region, the pre-variety germplasm Maple Grove ( L. lewisii ) and the cultivar 'Appar' ( L. perenne ) and related this variation to collection site geography and climate. Results from linear mixed models suggest there is extensive phenotypic variation among populations of Lewis flax within the Intermountain West. Using a multivariate approach, we identify a key suite of traits that are related to latitude and climate and may facilitate adaptation, including flowering indeterminacy, seed mass and stem number. These traits should be taken into account when considering the release of new germplasm for restoration efforts. We also find that Lewis flax seed contains desirably high amounts of alpha-linolenic acid and is otherwise mostly indistinguishable in fatty acid composition from oil-type varieties of domesticated flax ( L. usitatissimum ), making it a strong candidate for domestication. This study provides fundamental knowledge for future research into the ecology and evolution of Lewis flax, which will inform its use in both restoration and agriculture. Abstract : Common flax is grown worldwide as a food and fibre crop and is a short-lived annual. In the USA and Canada, its native perennial relative, Lewis flax, is used for ecological restoration and shows potential as an oilseed crop. Results from a common garden experiment in the Intermountain West show a key suite of Lewis flax traits that vary according to latitude and climate and may facilitate adaptation, including flowering time, seed mass and stem number. This study will benefit the use of Lewis flax in native plant restoration and will aid its domestication as a high-omega-3 oil source.